Determination Of The Risk Factors Of Pneumonia And The Evaluation Of The Cost Effectiveness Of Current Treatment Approach For Bacterial Pneumonia In Children Five Years And Younger - Abdulkader, Manhal A. (2011)
Pneumonia is a major cause of morbidity and mortality especially in developing countries. The prevention of pneumonia and its later disabilities can be achieved by the reduction of risk factors and evaluating subjects of high risk. Risk factors evaluation was one of the three aims of this retrospective age and gender matched case control study. A total of 260 children five years and younger diagnosed with pneumonia according to ICD-10 were involved, 43% of them (n = 113) having pneumonia of viral origin and 57% (n = 147) having bacterial pneumonia. Pneumonia risk factors were determined using Chi-square and Binary Logistic Regression. Incomplete immunization found to be the most significant risk predictor among all the analyzed factors (OR = 3.71, p< 0.001).